Identification and modeling of employee barriers while implementing lean manufacturing in small- and medium-scale enterprises. Issue 3 (5th March 2018) - Ramadas, T.; Satish, K.P.
Abstract : Purpose: The purpose of this paper is to present the factors associated with the employee barriers while implementing lean manufacturing within the small- and medium-scale enterprises (SMEs). Design/methodology/approach: The structural equation modelling approach is employed to develop the initial model drawing a sample survey of 133 small and medium enterprises. The result of the study shows that the lack of well-trained and experienced staff, lack of knowledge about existing specialist, cultural resistance to change are acting as the employee barriers while implementing lean manufacturing in SMEs. Then, a further study has been conducted to develop the employee barrier model with these three factors and its contributing variables using specification search representing the sample of 117 small and medium enterprises using the following fit function criteria: Chi-square (C), Chi-square-df (C-df), Akaike information criteria, Browne-Cudeck criterion, Bayes information criterion, Chi-square divided by the degrees of freedom (C/df) and significance level ( p ). Findings: The lack of well-trained and experienced staff, lack of knowledge about existing specialist, and cultural resistance to change with 19 associated elements were considered in the questionnaire. Specification search was carried out to build up the model on the collected data from 117 SMEs. The results of the specification search identified that these three factors with 15 key variables are significant to employee barrier while implementing lean manufacturing in SMEs. Research limitations/implications: The limitation of the study was that the sample size of the study was relatively small for further research, large sample size more than 117 are to be expected. Practical implications: The present study has explored an unfocused area of lean implementation in small and medium enterprises. The results obtained from the study are expected to help researchers, academics, and professionals for the further studies in the domain of lean manufacturing. Social implications: To implement and understand the lean manufacturing system, government of the many countries around the world are helping and encouraging by providing financial assistance for training professionals and establishing professional associations. However, many industries are not successful in lean implementation. This research work provides to develop a strategy to tackle employee barriers for successful lean implementation. Originality/value: Very little research has been carried out exploring employee barriers while implementing lean manufacturing in SMEs. This paper will provide value to academics, researchers and practitioners of lean by way of providing insight into significant employee barriers for lean implementation, especially in Indian industries.